Expression of Autophagy-Related Factors LC3A and Beclin 1 and Apoptosis-Related Factors Bcl-2 and BAX in Osteoblasts Treated With Sodium Fluoride - Xu, Lin; Deng, Chaonan; Zhang, Ying; Zhao, Lina; Linghu, Yan; Yu, Yanni (Frontiers in Physiology, 2021)
Objective: This study aimed to analyze the expressions of autophagy-related factors light chain 3 alpha (LC3A) and Beclin 1 and apoptotic factors B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X (Bax) in primary osteoblasts treated with sodium fluoride (NaF). Methods: Osteoblasts were extracted from Sprague–Dawley rats and treated with 0, 2.5, 5, and 10 mg/L NaF solutions, followed by 10 mmol/L 3-methyladenine (3-MA) for 24 hours. The apoptotic rate was determined by flow cytometry, and the expressions of the autophagy- and apoptosis-related factors were measured by Western blotting and real-time quantitative PCR. Results: The mRNA expressions of LC3A, Beclin 1, and Bax in the fluoride-treated osteoblast group were higher than those in the control group, while the protein expressions of those factors in the treated group were significantly higher compared to those in the control group. However, the Bcl-2 protein expression in the fluoride-treated osteoblasts was significantly decreased compared to that in the control cells. After the 3-MA treatment, the protein expressions of LC3A, Beclin 1, and Bcl-2 were significantly decreased compared with those of the NaF-treated group, whereas the expression level of Bax was increased. Moreover, the apoptosis rate was increased after the addition of the 3-MA inhibitor. Conclusion: The NaF stimulation promoted autophagy and apoptosis of the osteoblasts, suggesting the involvement of fluoride damage in these processes.